The Economic Analysis of Fisheries Management of Big Pelagic Fish in WPPNRI 715 - Riadi, Septa; Susanti, Annis; Nur Arkham, Muhammad (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Fisheries management is essential in striving for fish resources to be utilized optimally and sustainably and have a welfare impact. WPPNRI 715 is one of Indonesia's eleven fisheries management areas with the most significant potential in big pelagic fish with high economic value. The aim of this study was to estimate the economic value in the management of large pelagic fisheries in WPPNRI 715. The result of the research can show utilization of big pelagic fish in WPPNRI 715 is good condition and has not exceeded the Maximum Sustainable Yield (MSY) value. Additionally, economically the benefits are still in good condition. The optimal production (MSY) of big pelagic fish in WPPNRI 715 is 421 872, 11 tons. Maximum profit MEY is Rp3 065 588,97 trillion with the actual effort of 470 609 trips where optimal effort is sustainable (MSY) of 861 131 trips and economically optimal effort (MEY) of 554 902 trips. Based on the results of the study, it was stated that there were economic benefits in the utilization of large pelagic fish resources in WPPNRI 715.